2021
DOI: 10.1038/s41598-020-77924-z
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning-based model for screening and staging pneumoconiosis

Abstract: This study aims to develop an artificial intelligence (AI)-based model to assist radiologists in pneumoconiosis screening and staging using chest radiographs. The model, based on chest radiographs, was developed using a training cohort and validated using an independent test cohort. Every image in the training and test datasets were labeled by experienced radiologists in a double-blinded fashion. The computational model started by segmenting the lung field into six subregions. Then, convolutional neural networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…In this study, the dataset of 1760 DR chest radiographs comes from multiple centers and multiple devices, and the research results are more comprehensive. Besides, to our knowledge, our dataset is larger than those considered in the past investigations [ 16 , 17 , 20 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the dataset of 1760 DR chest radiographs comes from multiple centers and multiple devices, and the research results are more comprehensive. Besides, to our knowledge, our dataset is larger than those considered in the past investigations [ 16 , 17 , 20 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stage II is defined as: level 2 or 3 profusion of small opacities presented in four subregions or more. Stage III is defined as: large opacities presented [ 22 ]. Exclusion criteria for this study were as follows: subjects with other inflammatory diseases, other fibrotic diseases, other pulmonary diseases, such as chronic obstructive pulmonary disease (COPD), active tuberculosis, pneumonia and pulmonary heart disease and autoimmune disorders.…”
Section: Methodsmentioning
confidence: 99%
“…In the most recent computer vision applications, CNN has been used in many fields, including medical image analysis, which achieved outstanding state-of-the-art performances [ 98 , 99 ]. This study only found eight research articles based on the use of CNN to detect CWP in CXR in which non-texture features were extracted from the lung image [ 49 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. Zheng et al [ 73 ] investigated the CAD of CWP with the CXR films dataset, which indicated that traditional texture analysis is not enough to diagnose.…”
Section: Analysis Of Returned Articlesmentioning
confidence: 99%
“…They also verified the non-textured feature performances with older versions of CNN, for example, LeNet [ 101 ] and AlexNet [ 102 ]. Zhang et al [ 67 ] investigated the non-textured feature’s performances with two groups of radiologists. They found that the ResNet [ 103 ] model extracted the proper features from the six sub-regions in the lung, which outperformed the radiologists.…”
Section: Analysis Of Returned Articlesmentioning
confidence: 99%
See 1 more Smart Citation